Investigating biomarkers for personality alterations in temporal lobe epilepsy patients: based on peripheral inflammatory indices, electroencephalography, and neuroimaging - Jia Wang; Fuchi Zhang; Yunshan Zhou; Xiulin Zhang; Jianyang Xu; Shouyong Wang; Chengbing Huang; Taipeng Sun; Hugen Xu; Xiangsong Shi (Frontiers in Psychiatry, 2025)
BackgroundThe investigation of personality alterations in temporal lobe epilepsy (TLE) constitutes a complex and demanding field of research. These alterations may be intricately linked to neuroinflammation, imaging changes, and electrophysiological irregularities.ObjectiveThis study aims to explore the potential value of the peripheral inflammatory indices, video electroencephalogram (VEEG), hippocampal magnetic resonance imaging (MRI) as biomarkers for personality changes in patients with TLE.MethodsA total of 110 individuals with TLE were categorized into two groups: 55 patients exhibiting personality alterations and 55 patients without personality abnormalities. A supplementary cohort of 150 healthy individuals was enlisted as a control group. Demographic information, clinical attributes, inflammatory biomarkers, hippocampus MRI, and video EEG data were gathered and subjected to statistical analysis utilizing SPSS software.ResultsIn comparison to the healthy control group, patients with TLE demonstrated markedly reduced counts of neutrophils, lymphocytes, and platelets, although the monocyte-to-lymphocyte ratio (MLR) was considerably elevated (all P<0.05). The cohort exhibiting personality alterations demonstrated an extended disease duration, an elevated incidence of hippocampal sclerosis or atrophy on MRI, and a reduced rate of monotherapy relative to the cohort without personality alterations (P<0.05). Binary logistic regression research indicated no significant correlation between personality alterations in patients with TLE and neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), MLR, systemic immune-inflammation index (SII), or pan-immune-inflammation value (PIV).ConclusionsMLR was markedly elevated in patients with TLE relative to healthy controls. Hippocampal sclerosis or atrophy constituted an independent risk factor for personality alterations in TLE, although monotherapy seemed to serve as a protective factor.